Representation of Language Functions in Habiburrahman El Shirazy’s Novel Pudarnya Pesona Cleopatra - Bela Audy Hayati; Gazali; Pratama Bayu Santosa; Agustan (Universitas Islam Negeri Palopo, 2025)
This research aims to outline the language roles found in the novel